(untitled) (Medical Forum Monthly, 2024)
Objectives: the objective of this study was to compare the use of weapon of offence in medico legal cases in urban area with the use of weapon in rural area in such cases. Study Design: Comparative study. Place and Duration of Study: A medico legal centre of an urban area of Shaheed Benazir Hospital Abbottabad was selected. The record of recorded cases was taken, researched and record was formed on Performa’s, the total time interval of the recorded cases in Performa’s was of two months (February to March 2011). Materials and Methods: It is also a record based research retrospectively like the study of rural area, 55 cases recorded in a MLC centre of urban area of Abbottabad were recorded from the previously registered cases consecutively on designed Performa, Data of weapon used along with preliminary data was recorded of these registered cases and analysed. Results: Among the 55 cases the weapon of offence used was Blunt, Sharp, Pointed, Fire Arm, RTA and others means thermal or chemical etc. The blunt weapon was used 33 ( 60% )cases, Sharp edged light weapon was used in 3 ( 5.5% ) cases, pointed weapon was used in 2 (3.6%) cases, Fire Arm in 8 (14.5%) cases, RTA cases were 8 (14.5%) and others in 1 (1.8%) cases. Conclusions: The study represents the true picture of the province and society, being a comparative study it shows that there is not much difference in the society as a whole, in urban study no female was victimized among these 55 cases, the perpetrator used weapon only against male victims, which again shows less involvement of female population in daily disputes like rural area, the incidence of using Blunt weapon was higher, and the cases suffering from FAI and RTA were equal.